Harmonic functions which are starlike of order β with respect to other points - Aini Janteng; Suzeini Abdul Halim; Maslina Darus (Hikari Ltd, 2008)
Let H denote the class of functions f which are harmonic and univalent in the open unit disc D = {z : |z| < 1}. This paper defines and investigates a family of complex-valued harmonic functions that are orientation preserving and univalent in D and are related to the functions starlike of order β(0 ≤ β < 1), with respect to other points. We obtain growth result, extreme points, convolution and convex combinations for the above harmonic functions.